Hydrogen storage performance of platinum supported carbon nanohorns: A DFT study of reaction mechanisms, thermodynamics, and kinetics - Chompoonut Rungnim (2018)
© 2018 Hydrogen Energy Publications LLC Platinum (Pt) is one of a robust hydrogen dissociative catalyst. However, the migration of dissociated hydrogens from Pt nanoparticles to carbon supports such as graphene and carbon nanotube are energetically unfavorable reactions. To enhance the hydrogen storage via migration mechanism, carbon nanohorn is applied as a support for Pt nanoparticles (Pt and Pt4). The H2 storage performance of Pt and Pt4 supported on the mono-vacancy carbon nanohorn (vNH) has been investigated by using density functional theory calculations. The Pt and Pt4 firmly deposit at the vacancy site through the three strong Pt–C bonds with binding energies about −7.0 eV, which can prevent the metal desorption and migration. The mechanism of H2 storage starts with H2 adsorption followed by H2 spillover reaction. The calculation results reveal that the supported Pt nanoparticles are the active sites for H2 dissociative adsorption while the high curvature surface of carbon nanohorn is the active area for accommodating the migrated H atoms from the spillover reaction. Remarkably, the hydrogen spillover reactions over Pt– and Pt4-supported on vNHs in this study are spontaneous at room temperature with highly exothermic reaction energy. The fundamental understanding obtained from this study is beneficial for further design and synthesis of high-performance materials for H2 storage applications.